The role of extracorporeal photopheresis in the management of cutaneous T‐cell lymphoma, graft‐versus‐host disease and organ transplant rejection: a consensus statement update from the UK Photopheresis Society. (21st February 2017) - Alfred, Arun; Taylor, Peter C.; Dignan, Fiona; El‐Ghariani, Khaled; Griffin, James; Gennery, Andrew R.; Bonney, Denise; Das‐Gupta, Emma; Lawson, Sarah; Malladi, Ram K.; Douglas, Kenneth W.; Maher, Tracey; et al.
Summary: Extracorporeal photopheresis (ECP) has been used for over 35 years in the treatment of erythrodermic cutaneous T‐cell lymphoma (CTCL) and over 20 years for chronic and acute graft‐versus‐host disease (GvHD) and solid organ transplant rejection. ECP for CTCL and GvHD is available at specialised centres across the UK. The lack of prospective randomised trials in ECP led to the development of UK Consensus Statements for patient selection, treatment schedules, monitoring protocols and patient assessment criteria for ECP. The recent literature has been reviewed and considered when writing this update. Most notably, the national transition from the UVAR XTS ® machine to the new CELLEX machine for ECP with dual access and a shorter treatment time has led to relevant changes in these schedules. This consensus statement updates the previous statement from 2007 on the treatment of CTCL and GvHD with ECP using evidence based medicine and best medical practise and includes guidelines for both children and adults.